IMPLEMENTATION OF TACTICAL APPROACH: ITS INFLUENCE ON STUDENTS' PHYSICAL FITNESS IN PLAYING FUTSAL - Muhammad Rama Sanjaya; Oman Hadiana (Universitas Muhammadiyah Kuningan, 2025)
The use of tactical approaches in physical education focuses on understanding strategy and decision-making in the game, beyond mere technical skills. This study was conducted at SMPN 1 Darma with the aim of analyzing the effect of tactical approaches on students' physical fitness. The method used was an experiment with a pretest-posttest design, involving 20 futsal extracurricular students as a saturated sample. The results showed that students who were trained with a tactical approach experienced a significant increase in physical fitness, especially in the aspects of endurance, agility, and coordination. This increase was due to the active involvement of students in activities that required problem solving and decision making during the game. The implications of this study indicate that the tactical approach is effective as an alternative to physical education learning that can improve students' overall physical fitness and increase student motivation and involvement in training because of its active, challenging nature, and encourage teamwork and problem solving.